2019
DOI: 10.1016/j.jcot.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Periarticular injection and continuous femoral nerve block versus continuous femoral nerve block alone on postoperative opioid consumption and pain control following total knee arthroplasty: Randomized controlled trial

Abstract: Continuous femoral nerve block (CFNB) has been used to prevent the breakthrough pain after total knee arthroplasty (TKA). Multimodal drug injection (PMDI) has also been shown to decrease opioid consumption and pain. We investigated whether the use of PMDI further improves analgesic and rehabilitation outcomes when used in conjunction with CFNB. This is a prospective randomized controlled study of 44 patients undergoing primary TKA. The treatment group (n = 23) received a PMDI of combined ropivacaine, epinephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Postoperatively, multimodal analgesia includes pharmacologic agents, neuraxial anesthesia, PNB, and PCA, each of which will be described below. Compared with a monotherapy, multimodal analgesia provides superior postoperative pain relief to promote recovery of the knee, and reduce opioid consumption and related side effects. Consequently, multimodal analgesia is used widely for perioperative pain control in patients undergoing TKA.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperatively, multimodal analgesia includes pharmacologic agents, neuraxial anesthesia, PNB, and PCA, each of which will be described below. Compared with a monotherapy, multimodal analgesia provides superior postoperative pain relief to promote recovery of the knee, and reduce opioid consumption and related side effects. Consequently, multimodal analgesia is used widely for perioperative pain control in patients undergoing TKA.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
“…In an attempt to relieve severe postoperative pain, several routine approaches have been proposed, such as use of preemptive analgesia, opioids, cyclooxygenase‐2 inhibitors, epidural anesthesia, peripheral nerve blockade, local infiltration analgesia, patient‐controlled analgesia, and multimodal analgesia. Adequate postoperative analgesia could not only reduce pain, opioid consumption, and, consequently, opioid‐related adverse events, but also reduce length of hospital stay and costs, and improve rehabilitation and patient satisfaction. Therefore, it is necessary for surgeons to fully understand current anesthetic and analgesic regimens for TKA to improve patient outcomes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…36 Specifically, studies have shown associations between better postoperative pain management after TKA and patient satisfaction. 37-39 As such, it is especially interesting that this study showed significantly lower levels of pain in the OP ASC setting and significantly higher levels of satisfaction of pain control with respect to TKA. This demonstrates some of the reasons, which have not previously been studied, on why an OP ASC may offer advantages over IP settings with respect to patient satisfaction after TKA.…”
Section: Discussionmentioning
confidence: 68%
“…However, effective pain control remains an issue due to its subjective nature and patient diversity [ 4 ]. Several postoperative analgesic regimens are utilized to maximize analgesic effects and minimize possible undesired adverse events [ 3 ]. In the past, epidural analgesia was regularly used as postoperative analgesic regimen after TKA.…”
Section: Introductionmentioning
confidence: 99%